Ploidy study of chrysanthemum (Chrysanthemum morifolium) through PMC’s method - BALA, ANU; BALA, MADHU; SRIVASTAVA, PUJA; KHARE, VIKRANT (The Indian Journal of Agricultural Sciences, 2022)
Determination of the ploidy level of plants is utmost important for identification of species, selection of suitable parental lines and also to identify the relationships between species to determine the evolutionary patterns. In chrysanthemum species, chromosomes often have different degrees of differentiation, both between and within species. Total 30 genotypes of Chrysanthemum (Chrysanthemum morifolium Ramat.) were used to study the cytology in the Department of Floriculture and Landscaping and Department of Plant Breeding and Genetics, PAU, Ludhiana during 2019 with the objective to find out the genetic variation among the diverse genotypes of chrysanthemum. The ploidy level of 30 chrysanthemum genotypes was studied through meiotic study of pollen mother cells and for this study of meiotic chromosomes, stage and timings of bud collection is very much important. A range of ploidy level was encountered in chromosomal study of selected chrysanthemum germplasm and ploidy level was 2n= 52–116. This study indicated that polyploidy variation was found in all varieties of chrysanthemum selected for study. The elucidation of ploidy level of various crops and species provides foundation for understanding their genetic background, therefore, the results of present study will be further helpful for germplasm conservation of chrysanthemum flower crop.